EPN:encryption padding for NTRU with provable security - MU Ning-bo; HU Yu-pu; WANG Bao-cang (Tongxin xuebao)
Known as the fastest public key cryptosystem available now,the provable security of NTRU has not been solved well.an encryption padding,called EPN was designed,for NTRU.Under the full domain one wayness assumption of NTRU,EPN had been proved indistinguishable from adaptive chosen ciphertext attack by using the Game-Hopping technology in the random oracle model.Compared with present NAEP available,implement efficiency of EPN improves by 25%.